DNA barcoding of gamat and timun laut species from Pangkor Island using 16S mitochondrial ribosomal RNA gene - K., Kamarudin; Mohamed Rehan, Maryam; Ramly, Nur Zazarina; Mohamed Rehan, Aisyah (2015)
This study aimed to barcode a commercial sea cucumber (Echinodermata: Holothuroidea) or gamat species i.e., Stichopus horrens Selenka, 1867Error! Reference source not found. or dragonfish, and a timun laut species i.e., Holothuria (Mertensiothuria) leucospilota (Brandt, 1835) or white threads fish from Pangkor Island, Perak Darul Ridzuan, Malaysia applying partial DNA sequencing of non-protein-coding 16S mitochondrial ribosomal RNA gene. Pangkor Island in the north region of Peninsular Malaysia is well known for its traditional production industry of air gamat (body fluid extracts) and minyak gamat (lipid extracts). The phylogenetic analyses using Neighbour-Joining method and Maximum Likelihood method supported the morphospecies status of H. leucospilota and S. horrens. Despite the fact that more specimens and different molecular approaches are required to produce better conclusive results, the current findings gave a better insight of the importance of morphological approach and 16S mitochondrial rRNA gene sequencing in identification of the two Malaysian sea cucumber species from Pangkor Island. Furthermore, the gene barcodes can be used as the commercial species standard or reference samples in determining the species identities of processed sea cucumbers from Malaysian markets.